Population distribution and threats to sustainable management of selected non-timber forest Products in tropical lowland rainforests of South Western Nigeria (2013)
Uncontrolled harvesting of non-timber forest products (NTFPs) poses a serious risk of extermination to several of these species in Nigeria. Yet, there is a paucity of information on the distribution, population status and sustainable management of NTFPs in most of the tropical lowland rainforests. We, therefore, assessed the population, distribution and threats to sustainable management of NTFPs within the tropical lowland rainforests of Omo and Shasha Forest Reserves, south western Nigeria. Data were obtained through inventory surveys on five top priority species including: bush mango (Irvingia gabonensis (Aubry-Lecomte ex O'Rorke) Baill), African walnut (Tetracarpidium conophorum (Mull. Arg.) Hutch. & Dalziel syn. Plukenetia conophora), chew-stick (Massularia acuminata (G. Don) Bullock), fever bark (Annickia chlorantha Setten & P.J.Maas syn. Enantia chloranta) and bush pepper (Piper guineense Schumach. & Thonn.). Purposive and stratified random sampling techniques were used for the inventory. Each forest reserve was stratified into three, viz: less disturbed natural forest (for areas that have been rested for at least ten years), recently disturbed natural forest (for areas that have suffered one form of human perturbation or the other in the last five years), and plantation forest (for areas carrying forest plantation). Data were collected from eighteen 10 m×500 m belt transects located in the above strata. The species were generally fewer in both plantation and recently disturbed natural forest than the less disturbed natural forest, suggesting that forest disturbances (habitat modification) for other uses may have an effect on the occurrence and densities of the NTFPs. Exceptions to this trend were found for P. guineense and T. conophorum, which were fairly common in both plantation and recently disturbed natural forest. Among three tree NTFP species (i.e. I. gabonensis, M. acuminata and A. chlorantha), only I. gabonensis showed a significant difference in overall DBH size classes for both reserves (t=-2.404; df =21; p=0.026). Three tree NTFP species in both reserves further showed differences from the regular patterns of distribution of trees. The fairly regular reverse J-shaped size class distribution observed for M. acuminata in the study sites, however, suggests a recuperating population. In general, destructive harvesting of species, logging operations, low population size, narrow distribution ranges and habitat degradation are the major threats to the population of NTFPs in the study area. The implications of our findings for sustainable management of NTFPs in the study area are discussed and recommendations are made for a feasible approach towards enhancing the status of the species.